A SPORTS COACHING PERFORMANCE INSTRUMENT EMPLOYING 3CâS OF THE UNIVERSITY OF SANTO TOMAS - Porto, Jerome A.; Empaynado-Porto, Analin B.; Santarin, Victor B.; Belecina, Rene R (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2016)
The sports coaching career have made a long way in terms of its contribution to the development of athletes. The career is no longer focused solely on better performance and skills but more importantly coaching should promote values and character formation among athletes during training and actual competition. The purpose of this study was to develop a sports coaching performance instrument employing the 3 Core Competencies of the University of Santo Tomas namely: Competence, Commitment, and Compassion. The study is a descriptive-developmental research. The process of instrument development employed four stages such as Stage 1: Planning - where the indicators were determined; Stage 2: Creation of the Table of Specification - where the components were identified; Stage 3: Construction of the Items and Stage 4: Evaluation through Content Validation, Item Analysis and Establishment of Reliability. Eight components were identified and were categorized to the Core Competencies of the University. The components are: 1. Knowledge of the Sport, 2. Leadership, Personal and Professional Qualities 3. Coaching Performance and Experience which were categorized under Competence 4. Code of Ethics and Conduct for Sports Coaches, 5. Interpersonal and Intrapersonal Relationship, 6. Coach Development, 7. Effective Communication which were categorized under Commitment; and 8. Character and Moral Development which were categorized under Compassion. Content validations were done by two administrators, six coaches and one UST Professor and two hundred student-athletes served as respondents to the instrument. The instrument established a reliability of 0.971 alpha coefficient and validity of 0.83 correlation coefficient.The developed evaluation instrument could pave the way for an evaluation process that is objective and impartial. As such, it is highly recommended to UST administrators as well as to other Dominican learning institutions especially in the process of retention, hiring and promotion of their sports coaches.